The perceptions of external auditors on the relationship between audit fees and audit quality - Hasan Mansur; Abdul Aziz Abdul Rahman; Abdelrhman Meero; Ahmad Shatnawi (Cogent Business & Management, 2022)
Audit fees are deemed as one of the factors that might influence the perceptions of public toward external auditors. The problem statement concentrated if there is a significant relationship between audit fees and audit quality through the mediators: total assets, origin of company, audit-firm size, complexity of operation in a company and auditor industry based on the perceptions of the external auditors. Therefore, this study aimed to investigate the perceptions of external auditors on the relationship between audit fees and audit quality. A survey questionnaire contains 18 items distributed to 90 external auditors, 73 were returned yielding 81% responses rate. Descriptive analysis and hierarchical regression were used to analyze data and test the hypotheses. The study revealed that there is insignificant relationship between audit fees and audit quality in case there is no mediators. Moreover, results revealed that after using five mediators (total assets, origin of a company, audit firm-size, complexity of operations, auditor industry) there is a significant relationship on the relationship between audit fees and audit quality in terms of audit firm-size as a mediator. In contrast, the study found that there are insignificant relationships between audit fees and audit quality in terms of the other mediators such total assets, origin of a company, complexity of operations, auditor industry. The results showed the audited companies/clients in Jordan are affected of the halo of big-4 audit firms regardless the factors that might play a big role in enhancing the quality of audit process.
Keywords: M41; M42; 650; Audit; Audit quality; Audit fees; External auditor